2017
DOI: 10.4236/msa.2017.87036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Detergents on the Appearance of Automotive Clearcoat Systems Studied in an Outdoor Weathering Test

Abstract: The ability to predict the weathering performance of the clearcoat system over a short period of time is essential for the design and development of coating production. Thus, the primary objective of the present study is to investigate whether it is possible to predict the weathering performance of an automotive paint system through determination of surface roughness, R a , and microhardness before and after various weathering exposure times (0, 24, 168, 336, 504, 672 hours) and when employing two different de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The traces were autolevelled, set up to a linear least-squares (LLS) straight line and then filtered with a standard low-pass of 0.8 mm cut-off wavelength. More details of the surface roughness measurement procedure have been reported elsewhere [22][23][24][25][26][27][28][29][30][31]. The high precision, repeatability and reproducibility of this technology make it appropriate for reverse engineering (RE) and roughness measurement.…”
Section: Surface Profile Measurementsmentioning
confidence: 99%
“…The traces were autolevelled, set up to a linear least-squares (LLS) straight line and then filtered with a standard low-pass of 0.8 mm cut-off wavelength. More details of the surface roughness measurement procedure have been reported elsewhere [22][23][24][25][26][27][28][29][30][31]. The high precision, repeatability and reproducibility of this technology make it appropriate for reverse engineering (RE) and roughness measurement.…”
Section: Surface Profile Measurementsmentioning
confidence: 99%
“…The traces were auto-leveled, set up to a linear least-squares (LLS) straight line and then filtered with a standard lowpass of 0.8 mm cut-off wavelength and filter CR ISO. Details of the average surface roughness measurements procedure and calibration trials have been reported elsewhere [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In general, the calibration results showed that the cantilever beam system (stylus with beam) at only one end was a linear mass-spring system (R 2 > 0.999) under operational and environmental conditions, generally at 20°C ± 1°C temperature and 40% ± 5% relative humidity, with an absolute uncertainties value of < 1% and measurement resolution down to at worst 50 nm.…”
Section: Measuring Methodsmentioning
confidence: 99%